An automated method for serum magnesium estimation - Whitmore, D. N. (1964)
An automated method for magnesium determination in serum is described using conventional AutoAnalyser equipment. The method gives results comparable with those obtained by the flame photometer. The method may prove particularly useful with subnormal serum magnesium levels.